2011
DOI: 10.1093/czoolo/57.4.477
|View full text |Cite
|
Sign up to set email alerts
|

No evidence of contagious yawning in the red-footed tortoise Geochelone carbonaria

Abstract: Three hypotheses have attempted to explain the phenomenon of contagious yawning. It has been hypothesized that it is a fixed action pattern for which the releasing stimulus is the observation of another yawn, that it is the result of non-conscious mimicry emerging through close links between perception and action or that it is the result of empathy, involving the ability to engage in mental state attribution. This set of experiments sought to distinguish between these hypotheses by examining contagious yawning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…These two experimental studies reveal the presence of contagious yawning in budgerigars in a controlled laboratory setting, corroborating a previous observational report assessing the temporal distribution of yawns in an undisturbed flock (Miller et al 2012b). The experiment in Study 1 provides an ecologically valid measure of social contagion utilizing the signaling of a live demonstrator producing real yawns (improving upon Wilkinson et al 2011). Temporally classified contagious yawns during these trials (i.e., those occurring within 5 min of a yawn from the matched pair) occurred more than three times as often when the birds could see one another, whereas there was no difference in the frequency of spontaneous yawning across visibility conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These two experimental studies reveal the presence of contagious yawning in budgerigars in a controlled laboratory setting, corroborating a previous observational report assessing the temporal distribution of yawns in an undisturbed flock (Miller et al 2012b). The experiment in Study 1 provides an ecologically valid measure of social contagion utilizing the signaling of a live demonstrator producing real yawns (improving upon Wilkinson et al 2011). Temporally classified contagious yawns during these trials (i.e., those occurring within 5 min of a yawn from the matched pair) occurred more than three times as often when the birds could see one another, whereas there was no difference in the frequency of spontaneous yawning across visibility conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Video-induced yawning has also been reported in stumptail macaques (Macaca arctoides; Paukner and Anderson 2006), but this response also cooccurred with heightened self-directed behaviors and thus appears to be due to social tension or stress rather than contagion. Species that have thus far failed to show contagious yawning in an experimental design include bonobos (Pan paniscus), orangutans (Pongo abelii), and gorillas (Gorilla gorilla) in response to both conspecific and human yawns (Amici et al 2014), and domesticated dogs and redfooted tortoises (Geochelone carbonaria) in response to conspecifics (Harr et al 2009;Wilkinson et al 2011). …”
Section: Introductionmentioning
confidence: 99%
“…While CY has been reported for stumptailed macaques, Macaca arctoides , elevated levels of concomitant self-directed scratching, suggested that the yawns derived from tension, rather than contagion [15]. The only solitary species tested for CY, the tortoise, Geochelone carbonaria [16] has shown no evidence of contagion. While the ultimate function of yawning remains disputed (for a review, see [17]), it has been suggested to carry thermorgulatory [18] and non-verbal communicative functions, and its contagiousness to serve the adaptive function of synchronizing group behaviour [19], with respect to arousal [20] and attention [21].…”
Section: Introductionmentioning
confidence: 98%
“…Although indistinguishable in the motor action pattern described above, a number of important factors, in addition to their triggers (i.e., physiological vs. social), differentiate these two types of yawns. Spontaneous yawns, or similar mandibular-gaping patterns, appear to be a phylogenetically old and conserved across vertebrate classes 10 , while contagious yawning is a more recently derived feature present in only a few highly social species 11,12 . Consistent with this view, these two responses show distinct ontogenies, with spontaneous yawns emerging early on within intrauterine development in humans 13 , while contagious yawns do not appear until early childhood 14 .…”
Section: Introductionmentioning
confidence: 99%